2021
DOI: 10.1038/s41598-021-83335-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of 3D scanning in the periorbital region

Abstract: The reproducibility of scanning in the periorbital region with 3D technology to enable objective evaluations of surgical treatment in the periorbital region was assessed. Facial 3D-scans of 15 volunteers were captured at different time points with a handheld Artec Space Spider structured light scanner. Two scans were made with a one minute interval and repeated after 1 year; for both a natural head position and with the head in a fixation-device. On assessing the area between the eyelashes and eyebrows, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The results showed that the Artec Space Spider system had the lowest RMSE and the smallest MSD among the three systems tested. This is consistent with previous studies that have also found the Artec system to have high accuracy and reliability 8, 19 . The Bellus3D Dental Pro application had the highest deviation from the ground truth model (MSD = 0.46 mm), which is in line with some previous studies that have reported limitations with this system 20 .…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that the Artec Space Spider system had the lowest RMSE and the smallest MSD among the three systems tested. This is consistent with previous studies that have also found the Artec system to have high accuracy and reliability 8, 19 . The Bellus3D Dental Pro application had the highest deviation from the ground truth model (MSD = 0.46 mm), which is in line with some previous studies that have reported limitations with this system 20 .…”
Section: Discussionsupporting
confidence: 93%
“…The Artec Space Spider’s results were found to be most valid compared to Artec Eva, Vectra H1, Bellus and SNAP after scanning plaster statues with balls attached; the linear measurements were used for comparison purposes 13 . The reliability of scanning the peri-orbital region with the Artec Space Spider was excellent, at 0.1–0.2 cmm 14 .…”
Section: Discussionmentioning
confidence: 99%
“…To ensure scanning accuracy, we chose to scan with EinScan SP (Shining 3D, Hangzhou, China), which provides an accuracy better than 0.05 mm [28]. Its accuracy is below clinically accepted 1 mm measuring error threshold for both the natural head and fixated positions per Hollander et al [29]. This 3D scanning process generates a Wavefront (.obj) file and an image file that includes the mesh and texture data, which provides visual details and surface characteristics of the object.…”
Section: Methodsmentioning
confidence: 99%